2004
DOI: 10.1182/blood-2003-10-3719
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell expression of tissue factor in sickle mice is augmented by hypoxia/reoxygenation and inhibited by lovastatin

Abstract: Abnormal tissue factor (TF) expression has been demonstrated on blood monocytes and circulating endothelial cells in humans with sickle cell anemia. We have now studied sickle transgenic mice to help define the biology of endothelial TF expression in sickle disease. Using immunostaining of tissue sections, we find that this is confined almost exclusively to the pulmonary veins. About 15% and 13% of these exhibit TF-positive endothelium in the wild-type normal mouse and the normal human hemoglobin (HbA)-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
192
1
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 173 publications
(208 citation statements)
references
References 53 publications
8
192
1
2
Order By: Relevance
“…Thus, the relevant effect of H/R on triggering TF expression is exerted early after cessation of hypoxia, in the first few hours of the reoxygenation period, consistent with our previous observations of many other parameters post-H/R [4,5,6], even though maximal expression of actual TF protein requires many hours longer [3]. These results suggest not only that NO may be of therapeutic benefit but also that endogenous NO could be a regulator of TF expression, as influenced by inflammation.…”
Section: Modulation By Inhaled Nosupporting
confidence: 91%
See 4 more Smart Citations
“…Thus, the relevant effect of H/R on triggering TF expression is exerted early after cessation of hypoxia, in the first few hours of the reoxygenation period, consistent with our previous observations of many other parameters post-H/R [4,5,6], even though maximal expression of actual TF protein requires many hours longer [3]. These results suggest not only that NO may be of therapeutic benefit but also that endogenous NO could be a regulator of TF expression, as influenced by inflammation.…”
Section: Modulation By Inhaled Nosupporting
confidence: 91%
“…The nature of these mice and the methods used to genotype them have been described [3]. We previously found that this hBERK1 mouse is very similar to the most-severe BERK mouse in having high TF expression even at ambient air without H/R [3].…”
Section: Methodsmentioning
confidence: 86%
See 3 more Smart Citations